Linguocultural realization of epistemic modality in Uzbek and English: phraseological units, evidentiality, and cultural schemas - Turakulova, Dilafruz Mamatsoli qizi (The Lingua Spectrum, 2026)
This article examines how epistemic modality – the linguistic encoding of the speaker’s level of confidence, doubt, and (dis) belief in a proposition - is realized in Uzbek and English. The analysis combines the functional-semantic perspective of modality with a discussion of the evidential-epistemic boundary and a cultural-conceptual view of language as collective knowledge. The data set is drawn from literary discourse, primarily from the Uzbek novel “Shaytanat” by Tohir Malik and the English novel “The Godfather” by Mario Puzo, supplemented with illustrative examples fitting the genre. The units were categorized into three epistemic fields (certainty, doubt/suspicion, and uncertainty) and compared cross-linguistically. Results show that English typically marks epistemic stance through explicit lexical means – modal verbs, adverbs of manner, and first-person predicates (I think, I guess, probably), while Uzbek often favors indirect, interactionally sensitive strategies such as evidential verb forms, sentence-final particles (shekilli, bo‘lsa kerak), and culturally loaded fate-oriented expressions (Xudo xohlasa, nasib qilsa). These contrasts reflect different cultural schemas of knowledge, politeness, and responsibility in communication.